2000
DOI: 10.1089/152460900318623
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic Effect of a Daily Supplement for 1 Month of 200 mg Magnesium plus 50 mg Vitamin B6 for the Relief of Anxiety-Related Premenstrual Symptoms: A Randomized, Double-Blind, Crossover Study

Abstract: To investigate single and combined effects of daily dietary supplementation with 50 mg of vitamin B6 and 200 mg magnesium (as MgO) for one cycle for the relief of mild premenstrual symptoms, a randomized, double-blind, placebo-controlled, crossover design was used. Forty-four women with an average age of 32 years took part in the study. Each woman was randomly assigned, according to a Latin square design, to take consecutively all four of the following treatments daily for one menstrual cycle: (1) 200 mg Mg, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 6 publications
0
62
0
1
Order By: Relevance
“…Serum magnesium concentrations were used to indicate magnesium status in some studies, 11,15 but their reliability is questionable. 16,17 Clinical trials have suffered from limited sample sizes, 10,11 the use of the supplement magnesium oxide 18 (which is poorly absorbed), 17 and restrictive inclusion criteria. 11 With varying outcomes, different populations and age ranges, and limited sample sizes, consensus on the relationship between magnesium intake and depression has not been reached.…”
mentioning
confidence: 99%
“…Serum magnesium concentrations were used to indicate magnesium status in some studies, 11,15 but their reliability is questionable. 16,17 Clinical trials have suffered from limited sample sizes, 10,11 the use of the supplement magnesium oxide 18 (which is poorly absorbed), 17 and restrictive inclusion criteria. 11 With varying outcomes, different populations and age ranges, and limited sample sizes, consensus on the relationship between magnesium intake and depression has not been reached.…”
mentioning
confidence: 99%
“…Moreover, some trials have shown the effect of magnesium on the treatment of psychological disorders (De Souza, Walker, Robinson, & Bolland, 2000;Heiden et al, 1999). A systematic review also suggests that magnesium may be effective in depression therapy, but further studies are required (Derom, Sayon-Orea, Martinez-Ortega, & Martinez-Gonzalez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many trials worldwide (e.g. Williams et al 1985;Stewart 1987;London et al 1991;De Souza et al 2000) on the use of vitamin B 6 for this purpose. Wyatt and colleagues (1999) performed a systematic review including a meta-analysis on the topic involving nine randomized, controlled clinical trials of vitamin B 6.…”
Section: Non-pharmacologic Treatments Of Pmsmentioning
confidence: 99%